A Causal Relationship Model of the Influence of Information Technology Governance Processes on the Benefits Received by Thai Public Companies. Issue 1 (5th December 2017) - Sunthonwutinun, Wilai; Chooprayoon, Vasin
Abstract: This study applies the COBIT5 framework and the balanced scorecard approach to information technology governance (ITG) in public companies in Thailand. The objectives of the study are to develop and verify a causal relationship model of the influence of ITG processes on the benefits received by companies. The model is composed of four latent variables: learning and growth, internal processes, customers, and finances. A questionnaire was used to gather data from a sample of 497 chief ITG officers and auditors working in companies registered on the Stock Exchange of Thailand. Structural equation modeling was used to construct the model. The results showed that the model was consistent with the empirical data, with a chi‐square value of 190.85, a degree of freedom of 166, and a p‐value of 0.91. This pointed out that hypotheses of the model could be explained a structure model of ITG, which influence wealth of the companies up to 80 percent (R 2 = 80). It is reasonable to imply that ITG influences the benefits obtained by Thai public companies in terms of high capacity of employees, good internal processes, customer satisfaction, loyalty, and stable finances.